ANALISIS PENGARUH VARIABEL MAKRO EKONOMI TERHADAP KINERJA PASAR MODAL SYARIAH DI INDONESIA - Rahmi Wulandari; Yeniwati Yeniwati; Dewi Zaini Putri (Jurnal Ecogen, 2018)
This research aims to find out and analyze the influence of the peformance islamic capital market on inflation, exchange rates, interest rates and foreign direct investment in Indonesia. The type of research used is descriptive and associative research. The data in this study are secondary data from 2007-2016 Q1-Q4 with the quarter one to quarter four documentation and library data collection techniques.. Data analysis used is descriptive analysis and inductive analysis. In inductive analysis using the Ordinary least squares approach, there are several tests, namely: (1) Multicollinearity Test; (2) Autocorrelation Test; (3) Determination of heteroscedasticity; (4) Normality Test; (5) Multiple Leinear Analysis;Research results show that: (1) There is no significant effect of inflation on the islamic capital market; (2) There is an influence between the exchange rates that affect the islamic capital market; (3) There is no influence between interest rates (SBI) on the islamic capital market; (4) there is ian influence of foreign direct investment that affect the islamic capital market. Based on the results of this study it is suggested that the government should pay more attention to the condition of stock price movements in Indonesia Keywords: The peformance islamic capital market, inflasi, niliai tukar, suku bunga,, Foreign Direct Investment, Ordinary Least Squares  (OLS).